STRATEGI GURU DALAM MENGOPTIMALKAN PROSES PEMBELAJARAN MELALUI MODEL AKTIF DAN REFLEKTIF DI MTsN GOWA (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to describe the strategies used by teachers to optimize the learning process through active and reflective learning models at SMPN Gowa. The research employed a descriptive qualitative approach with data collected through in-depth interviews, classroom observations, and documentation. The research subject was selected purposively, focusing on a teacher who consistently implements active and reflective learning models in classroom activities. The findings reveal that the teacher begins the learning process with thorough planning by analyzing the Learning Outcomes (CP), Learning Objectives Flow (ATP), and student characteristics as the basis for selecting appropriate instructional strategies. In practice, the teacher applies several active learning models such as Problem-Based Learning, Think-Pair-Share, Project-Based Learning, and Game-Based Learning, all of which effectively enhance student participation and motivation. The teacher also integrates digital tools such as Quizziz and Canva to support creativity and increase student engagement. Evaluation is conducted through both formative and summative assessments, while reflective practices are carried out through teacher reflection journals and student feedback. Overall, the combination of active and reflective learning strategies is proven to be effective in improving student independence, conceptual understanding, and the overall quality of the learning process at SMPN Gowa.